Strategi Pemberdayaan UMKM Kuliner Berbasis Ekonomi Syariah di Sentral Kuliner Kaur - Putri, Fiona Hasdo; Sapitri, Ola; Hasanah, Uswatun (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Culinary Micro, Small, and Medium Enterprises (MSMEs) play an important role in the regional economy, especially in creating jobs and improving community welfare. This article aims to analyze the empowerment strategy of culinary MSMEs based on sharia economy in Kaur Culinary Center with a focus on the Sate Surabaya Etek Sangun business. This study examines the application of sharia economic principles, such as honesty, fairness, and avoidance of usury in business management, as well as business development and sustainability strategies through product innovation, marketing digitalization, and cooperation with sharia financial institutions. The results of the study indicate that the application of sharia economy has a positive impact on business sustainability, increasing competitiveness, and creating broader social value. In addition, empowerment of MSMEs through training, mentoring, and strengthening distribution networks are important keys in encouraging sustainable business growth. This research is expected to contribute to the development of policies and strategies for empowering MSMEs based on sharia economy in the region.